Thalassoporum longitrichum sp. nov., a marine epizoic cyanobacterium with anti-inflammatory potential, and the taxonomic reassessment of Limnothrix Meffert - C. Tenorio Rodas; G.S. Hentschke; F. Oliveira; G. Lopes; A. Duarte; J. Morone; A. Campos; V. Vasconcelos (Algal Research, 2026)

Evaluation of rapid evaporative ionization mass spectrometry (REIMS) relationships with biochemical markers of tenderness in beef Longissimus lumborum steaks - Kaitlyn R. Loomas; Dale R. Woerner; Ben M. Bohrer; Tyson R. Brown; Heather L. Bruce; Marcio S. Duarte; Bimol C. Roy; Yifei Wang; Katie Pedgerachny; Jerrad F. Legako (Meat Science, 2026)

Veterinary perspectives on biosecurity measures in small-scale farming systems across European countries: Results from a cross-national survey - F. Duarte; J. Prodanov-Radulović; B. Mehmedi; A. Piccirillo; M. Stukelj; E. Kldiashvili; V. Nedosekov; B. Milovanovic; N.D. Ayaz; R. Yildiz; S. Meling; I. Toftaker; et al. (Research in Veterinary Science, 2026)

Prior autonomous self-pollination as a reproductive assurance mechanism in a high-Andean orchid - Carlos A. Matallana-Puerto; João C․F. Cardoso; Laura J․Pérez Uscategui; Mariana O. Duarte (Flora, 2026)

Racial and ethnic disparities in environmental chemical exposures and hypertensive disorders of pregnancy: The ECHO-wide cohort study - Hongxiu Liu; Amii M. Kress; Emma X. Yu; Xuejuan Ning; Akhgar Ghassabian; Linda G. Kahn; Shilpi Mehta-Lee; Sara Brubaker; Akram Alshawabkeh; John Meeker; Carlos A. Camargo; Shakira F. Suglia; et al. (Environmental Pollution, 2026)

Unravelling the molecular mechanisms of vegetative-to-reproductive transition in Cynara cardunculus by RNA-Seq analysis - A. Paulino; I. Fernandes; R. C. Pires; A. Usié; A. Faustino; J. Santos; T. Brás; D. Rosa; O. S. Paulo; M. F. Duarte; L. Marum (Plant Molecular Biology, 2026)
Cynara cardunculus inflorescence plays a significant role in cheese manufacturing and human consumption due to the milk-clotting capacity and the production of edible immature capitula. Consequently, it is crucial to understand the complex cellular and molecular processes involved in the development of cardoon flowers. The current study used western wild cardoon in two developmental stages, vegetative and reproductive, to understand the molecular mechanisms mediating cardoon`s vegetative-to-reproductive transition. Transcriptome profiling identified 552 differentially expressed genes (DEGs) between vegetative and reproductive stages, with 321 upregulated in stage 4 (vegetative state) and 231 in stages 5/6 (reproductive state). Gene Ontology (GO) analysis revealed DEGs involved in biological processes such as oxidation-reduction, lipid metabolism, and defense responses. Metabolic pathways, including phenylpropanoid biosynthesis and anther/pollen development, were significantly enriched. Genes associated with lignin formation, flavonoid synthesis, and acetyltransferase activity were upregulated in the vegetative stage. At the same time, those related to flower development and sesquiterpene lactone biosynthesis were prominent in the reproductive stage. Transcription factors, including MADS-box and ethylene-responsive families, were critical in regulating developmental transitions. This study provides comprehensive insights into the morphological, chemical, and molecular dynamics of C. cardunculus across its phenological stages, underscoring the plant’s adaptability and potential for pharmaceutical and industrial applications. The findings highlight the importance of seasonal and developmental timing in optimizing the production of valuable secondary metabolites, such as cynaropicrin.

High meiofaunal diversity in the Azores revealed through DNA metabarcoding - Francesca Leasi; Nuno V. Álvaro; Luiz F. Andrade; Thiago Q. Araújo; Víctor Aramayo; Tom Artois; Will M. Ballentine; Franziska S. Bergmeier; Andrea Z. Botelho; Ariane Buckenmeyer; Ana T. Capucho; Irina Cherneva; et al. (Marine Biodiversity, 2026)
To advance understanding of meiofauna, key components of marine benthic ecosystems, an international team conducted a morphology-based taxonomic survey and workshop around São Miguel, the largest Azorean island, in 2019. The survey yielded critical baseline data on meiofaunal diversity and, despite taxonomic challenges that limited identification of certain taxa, laid a solid foundation for further research. To expand these findings, additional samples were analyzed using DNA metabarcoding, a powerful tool that assesses multiple facets of biodiversity, including richness, community composition, and phylogenetic diversity. Metabarcoding identified 480 meiofaunal amplicon sequence variants across 14 phyla, more than doubling the 180 taxa recorded through morphology alone. Of these, 298 (approximately 62%) belonged to phyla targeted during the morphology-based workshop. A comparison between the two approaches, focusing on clades addressed during the workshop, revealed overlapping but expanded patterns of diversity relative to morphology-based taxonomy. This consistency supports the metabarcoding’s ability to uncover meiofaunal diversity and underscores the importance of integrating both methods to achieve a more comprehensive understanding of biodiversity and ecological patterns. As the first metabarcoding study in the Azores, this work establishes a biodiversity baseline for a remote and understudied region, indicating greater benthic diversity than previously recognized. By revealing the complexity of these understudied ecosystems, this research contributes to document and support conservation of biodiversity in the Azores and emphasizes the need for further exploration of meiofaunal communities in isolated oceanic environments.

WABAD : A world annotated bird acoustic dataset for passive acoustic monitoring - Cristian Pérez‐Granados; Jon Morant; Kevin F. A. Darras; Oscar H. Marín‐Gómez; Irene Mendoza; Miguel A. Muñoz‐Mohedano; Eduardo Santamaría‐García; Giulia Bastianelli; Alba Márquez‐Rodríguez; Michał Budka; Gerard Bota; José M. De la Peña‐Rubio; et al. (Ecology, 2026)
Under the current global biodiversity crisis, there is a need for automated and noninvasive monitoring techniques that can gather large amounts of data cost‐effectively at various ecological scales, from local to large spatial scales. These data can then be analyzed to inform stakeholders and decision‐makers. One such technique is passive acoustic monitoring, which is commonly coupled with automatic identification of animal species based on their sound. Automated sound analyses usually require the training of sound detection and identification algorithms. These algorithms are based on annotated acoustic datasets which mark the occurrence of sounds of species inside sound recordings. However, compiling large annotated acoustic datasets is time‐consuming and requires experts, and therefore, they normally cover reduced spatial, temporal, and taxonomic scales. This data paper presents WABAD, the World Annotated Bird Acoustic Dataset for passive acoustic monitoring. WABAD is designed to provide the public, the research community, and conservation managers with a novel and globally representative annotated acoustic dataset. This database includes 5047 min of audio files annotated to species‐level by local experts with the start and end time and the upper and lower frequencies of each identified bird vocalization in the recordings. The database has a wide taxonomic and spatial coverage, including information on 91,931 vocalizations from 1192 bird species recorded at 72 recording sites in 29 recording locations (mainly countries) and distributed across 13 biomes. WABAD can be used, for example, for developing and/or validating automatic species detection algorithms, answering ecological questions, such as assessing geographical variations on bird vocalizations, or comparing acoustic diversity indices with species‐based diversity indices. The dataset is published under a Creative Commons Attribution 4.0 International license that permits redistribution and reuse on the condition that the original work is properly credited.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Ocean transport and vertical mixing connect Greenland's macroalgae to deep ocean carbon sinks - Daniel F. Carlson; Nobuhiro Suzuki; Ruben Carrasco; Karen Filbee-Dexter; Laura C. Gillard; Paul G. Myers; Ana M. Queirós; Jorge Assis; Carlos M. Duarte; Mikael Sejr; Dorte Krause-Jensen (Science of The Total Environment, 2026)

Conductive materials change the composition and activity of butyrate-degrading enrichment cultures with hydrogen as the main electron shuttle - Cátia S.N. Braga; João C. Sequeira; M. Salomé Duarte; Gilberto Martins; Inês A.C. Pereira; Luciana Pereira; M. Madalena Alves; Andreia F. Salvador (Journal of Environmental Sciences, 2026)

Out of sight, but not out of mind: Key issues regarding seafloor macrolitter monitoring - Georg Hanke; Miquel Canals; Ryota Nakajima; Melanie Bergmann; Francois Galgani; Daoji Li; George Papatheodorou; Christopher Kim Pham; Diva J. Amon; Michela Angiolillo; Lene Buhl-Mortensen; Alessandro Cau; et al. (Marine Pollution Bulletin, 2025)

Geological and geomechanical properties of soft rocks from the Lower Jurassic Vale Das Fontes Formation (Lusitanian Basin, Portugal): an exploratory study - P. F. Moreira; C. F. Rodrigues; L. V. Duarte; J. P. Temporão de Sousa; A. Vega y de La Fuente; A. Maldonado-Zamora; M. J. Lemos de Sousa; H. I. Chaminé (Mediterranean Geoscience Reviews, 2025)

Quantitative summary of nine years of fungicide efficacy data for managing white spot and protecting yield in maize - MonalisaC. De Cól; Karla Braga; AdrianoA.P. Custódio; Marcelo G. Canteri; Lucas H. Fantin; Carlos M. Utiamada; Hércules D. Campos; Dagma D. Silva-Araújo; Rodrigo V. Costa; InêsF.U. Yada; Aildson P. Duarte; Alfredo R. Dias; et al. (Crop Protection, 2025)

Ohmic heating for attenuation of Lactobacillus acidophilus LA-5 in Minas Frescal cheese: probiotic survival, biological activity, and in vitro antimicrobial activity - Cássia P. Barros; Tatiana C. Pimentel; Ramon Silva; Maria Carmela K.H. Duarte; Eliane T. Mársico; Erick A. Esmerino; Pedro Henrique C. Felix; Carlos Augusto F. Oliveira; Beatriz L. Valente; Marcelo Cristianini; Mônica Q. Freitas; Adriano G. Cruz (Food Research International, 2025)

Sex Drives Intraspecific Scaling of Home Range Size in Mammals - Aline Giroux; Denis Valle; Eliezer Gurarie; Marcus Vinicius Vieira; James D. Forester; Luca Börger; Raissa Sepulvida; Nicole Barbour; Erika G. da Rocha; Julia Oshima; Fernanda C. de Azevedo; Frederico G. Lemos; et al. (Ecology Letters, 2025)
Understanding variation in home range size (HR) provides important insights into the underlying ecological processes driving space use. However, it remains unclear whether the interspecific allometric scaling of mammals' HR can also be consistently observed within species and for both sexes. To address this knowledge gap, we GPS‐tracked 349 resident individuals across Brazil, encompassing 18 mammal species. We estimated individuals' HR and modelled intraspecific variation in HR against body mass (BM) and sex. While males showed a positive allometric scaling similar to interspecific findings reported in the literature (exponent = 1.23), females' BM had no statistically discernible relationship with HR. We suggest that males have greater energetic and evolutionary incentives to expand their HR with increasing BM, and more physical capacity to do so. Traditional studies on HR scaling that disregard individual sex may, in reality, reflect an average of two distinct patterns, while failing to accurately represent either one.

Examination of post-hatching starvation on oxidative stress response and larval life span in the marine ornamental shrimp, Lysmata seticaudata - Rafael C. Duarte; Daniel Acebes; Diana Madeira; Ruben X.G. Silva; Joana F. Fernandes; Fernando Ricardo; Ricardo Calado (Aquaculture, 2025)

Addressing Critical Fungal Pathogens Under a One Health Perspective: Key Insights from the Portuguese Association of Medical Mycology - R. Sabino; F. Antunes; R. Araujo; A. R. Bezerra; J. Brandão; C. Carneiro; A. Carvalho; D. Carvalho; I. C. Conceição; F. Cota Medeiros; C. Cruz; E. Duarte; et al. (Mycopathologia, 2025)
Fungal infections have emerged as a significant public health concern, especially with the increasing incidence of severe mycoses caused by pathogens such as Aspergillus fumigatus , Candida auris , Candida albicans , and Cryptococcus neoformans . These fungi, listed as critical priorities by the World Health Organization, pose a heightened risk due to rising antifungal resistance and their severe impact on immunocompromised individuals. This article, coordinated by the Portuguese Association of Medical Mycology, highlights the importance of adopting a One Health perspective to address fungal threats comprehensively. Drawing on interdisciplinary collaboration, the association aims to foster greater awareness, improve diagnostic capabilities, and stimulate research and public health policies in Portugal but also at global level. The paper outlines key strategies for surveillance, prevention, and innovation in fungal diagnostics and therapeutics. Moreover, it emphasizes the urgent need for national coordination and international cooperation in managing fungal infections, advocating for integrative approaches that link human, animal, and environmental health. By presenting a consolidated overview of current challenges and future priorities, this work seeks to enhance preparedness and response mechanisms in the face of escalating fungal threats.

Carbon footprint calculator for the Portuguese textile and clothing industry: development, application and validation - C. Duarte; J. V. Ferreira; I. P. L. Brás; M. E. F. Silva (International Journal of Environmental Science and Technology, 2025)
This study aimed to develop, implement, and validate a carbon footprint (CF) calculator to estimate greenhouse gas (GHG) emissions generated by Portugal´s Textile and Clothing Sector (TCS). To achieve this, the GHG Protocol and life cycle assessment (LCA) methodology were applied to develop the CF and analyse two textile and clothing companies (A and B). Validation was conducted using a self-assessment method that employed 2 online calculators and a LCA software. The CF calculator enables the quantification of the 3 scopes of GHG emissions. Scope 1 includes direct emissions from sources that are owned or controlled by the company, such as on-site energy, transportation of raw materials, finished products and personnel, as well as water usage. Scope 2 comprises indirect emissions from the use of purchased energy and Scope 3 includes emissions that occur across the supply chain, such as public water usage, wastewater, transportation, employee business travel, waste disposal and the end-of-life treatment of sold products. Avoided emissions and carbon offsetting measures and carbon sequestration strategies, were included. For Company A, energy consumption was the largest contributor to the CF, accounting for 76% of the contributions. In Company B, the waste component had the greatest impact on the CF, accounted for 38% of the contributions. In the validation process, the electricity and fuel consumption components yielded values that are consistent with those from other calculators. The calculator is a tool that TCS companies can use to quantify their emissions and define measures to reduce or offset their CF.

Aiding sea turtle conservation through coastal management - Jakob C. Christiaanse; Ad J. H. M. Reniers; Stefan G. J. Aarninkhof; Elias F. Ostertag; Ronel Nel; Carlos M. Duarte; José A. A. Antolínez (Frontiers in Marine Science, 2025)
Climate change and human activity pose increasing challenges to endangered sea turtles, which are key species in many marine ecosystems worldwide. Among these challenges are the flooding and erosion of nesting beaches. In this perspective, we argue that existing methods and tools from coastal science and management hold significant, yet underused, potential for sea turtle conservation. We introduce a stepwise framework for integrating sea turtle ecology and coastal management to address these coastal threats. The framework follows an Observe–Understand–Predict–Intervene cycle and links ecological thresholds, coastal processes, and management interventions across scales, from Regional Management Units (RMUs) to individual beaches. We illustrate how state-of-the-art monitoring, modeling, and nature-based solutions (NBS) can be embedded within this framework to inform when and how to intervene. Increased in-situ data collection and interdisciplinary collaboration will be critical to apply and refine this approach, thereby enhancing the long-term resilience of nesting habitats.

Late Quaternary population expansion in gray brocket deer [ Subulo gouazoubira (G. Fisher, 1814), Cervidae, Mammalia] in Brazil - Alex Hubbe; Mark Hubbe; Elver Luiz Mayer; Eliane Nunes Chim; Paulo Miguel Haddad‐Martim; Augusto S. Auler; Luís B. Piló; William J. Pestle; Alba Rey‐Iglesia; Isac dos Santos Antônio Machado; Paulo C. F. Giannini; Eluzai Dinai Pinto Sandoval; et al. (Journal of Quaternary Science, 2025)
There is little information about the changes in the abundance of mammalian species in South America during the late Quaternary, which is a key parameter to understanding past ecological and evolutionary dynamics. Here, we describe a conspicuous increase in the abundance of the gray brocket deer ( Subulo gouazoubira G. Fisher, 1814; Mammalia) during the late Quaternary in Brazil based on paleontological evidence. We studied the material retrieved from pitfall deposits in Cuvieri Cave (Brazil) representing three time intervals (Late Pleistocene, Pleistocene/Holocene transition, and Holocene). The deposits in this cave were previously characterized in terms of facies composition, chronology, and overall taxa and taphonomy. We combined previous data with taxonomic identification at the species level for deer (morphological and ancient DNA analyses), quantification of the number of individuals for large mammals (>10 kg), taphonomic analyses, and stratigraphic distribution of specimens. Our results show that while in the Late Pleistocene gray brocket deer corresponded to up to 18% of 38 individuals, in the Holocene they represented at least 82% of 78 individuals. We interpret this change in frequency as a considerable increase in abundance in the surroundings of the cave, after excluding major taphonomical biases. The causes for this phenomenon are uncertain but could have involved a surplus of food availability and predation release due to the late Quaternary extinction event.

Cleaning validation in pharmaceutical quality control laboratories: a structured protocol for contamination risk mitigation - Maria J. Moura; André D. Pereira; Daniel J. F. Santos; Ana G. Silva; Carla C. A. D. Paiva; Belmiro P. M. Duarte (DARU Journal of Pharmaceutical Sciences, 2025)
Background Cleaning activities are critical in pharmaceutical manufacturing to prevent cross-contamination of Active Pharmaceutical Ingredients (APIs). Traditionally, cleaning validation protocols have focused on production lines. However, there is a growing trend toward extending these protocols to Quality Control (QC) laboratories, encompassing both glassware and stainless-steel equipment. Objectives This paper presents a systematic approach for developing cleaning validation protocols specifically designed for QC laboratory equipment, aimed at improving cleaning effectiveness and ensuring regulatory compliance. Methods The proposed methodology includes: (i) identifying the worst-case API; (ii) performing recovery studies to optimize sampling methods and solvent selection; and (iii) employing statistical tools such as descriptive analysis and hypothesis testing to refine the protocol in line with current industry standards. Results A case study involving Oxcarbazepine demonstrates the application of the proposed protocol, evaluating surface contamination across various QC instruments and assessing detergent residues to validate cleaning effectiveness. Conclusion The proposed strategy provides a structured, statistically grounded framework for developing cleaning validation protocols in QC laboratories, promoting effective contamination control and adherence to regulatory standards. Graphical abstract

Highly Efficient Bio-Based Composites from Natural Fibers for Fauna Protection and Oil Spill Remediation - Islla M. C. Silvino; Beatriz S. Alves; Eduardo J. Fonseca; Vanderson B. Bernardo; Carmem L. P. S. Zanta; Josealdo Tonholo; Laís F. A. M. Oliveira; José L. S. Duarte; Leonardo M. T. M. Oliveira (Environmental Processes, 2025)

Au-TiO2 Catalysts for Enhanced Visible Light Photocatalysis for Sustainable Treatment of Textile Effluents - Raiane dos Santos; Evelle Duarte C. Oliveira; Ivana C. F. Araujo; Jhonanta N. Silva; Alan G. Câmara; Emerson F. M. da Silva; Ramón R. P. Garcia; Daniella C. Napoleão; Luciano C. Almeida (Water, Air, & Soil Pollution, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Evaluation of rapid evaporative ionization mass spectrometry (REIMS) for the prediction of slice shear force and quality grades in beef longissimus lumborum steaks - Kaitlyn R. Loomas; Dale R. Woerner; Ben M. Bohrer; Tyson R. Brown; Heather L. Bruce; Marcio S. Duarte; Bimol C. Roy; Yifei Wang; Katie Pedgerachny; Jerrad F. Legako (Meat Science, 2025)

Sustainability assessment of collagen extraction from fish skins: A comparative life cycle assessment of conventional and NADES-enhanced processes - Miguel P. Batista; Joana Ortigueira; Naiara Fernández; Frédéric B. Gaspar; Maria do Rosário Bronze; Ana Rita C. Duarte; Tiago F. Lopes (Journal of Environmental Chemical Engineering, 2025)

Testis transcriptomic analyses reveal the effects of an algae feed on sperm quality in Senegalese sole during the breeding season - F. Félix; C. Raposo de Magalhães; C. Marrero-Alemán; D. Duarte; P. Parente; E. Fatsini; C.C.V. Oliveira; E. Cabrita (Aquaculture, 2025)

Differentially spliced mitochondrial CYP419A1 contributes to ethiprole resistance in Nilaparvata lugens - B. Zeng; A.J. Hayward; A. Pym; A. Duarte; W.T. Garrood; S-F Wu; C-F Gao; C. Zimmer; M. Mallott; T.G.E. Davies; R. Nauen; C. Bass; et al. (Insect Biochemistry and Molecular Biology, 2025)

P14-06 The cytotoxicity of bortezomib in AC16 cardiac cells and possible therapeutic options involving Nrf2 - C. Vitorino-Oliveira; S. Kahremany; L. Nisim; M. Duarte-Araújo; F. Carvalho; A. Gruzman; V.M. Costa (Toxicology Letters, 2024)

P13-31 Characterization of human isogenic epithelial cell lines as a relevant tool to study colon carcinogenesis and interaction between genes and environment - A. Tête; L. Arnaud; H. Le Mentec; N. Poupin; I. Gallais; N. Tournade; C. Duarte Hospital; Y. Lippi; F. Mathevet; C. Pilati; G. Lefort; C. Lavau; et al. (Toxicology Letters, 2024)

P13-18 Succinate Dehydrogenase inhibitors (SDHi) fungicides induce mitochondrial dysfunction and metabolic reprogramming in human colon cells - C. Duarte-Hospital; A. Tête; K. Debizet; C. Rives; J. Imler; L. Galès; F. Bellvert; J. Dairou; R. Barouki; J.W. Shay; J. Bastin; S. Mouillet-Richard; et al. (Toxicology Letters, 2024)

Bacterial septicemia and herpesvirus infection in Antarctic fur seals (Arctocephalus gazella) stranded in the São Paulo coast, Brazil - Aricia Duarte-Benvenuto; A. M. Sánchez-Sarmiento; A. C. Ewbank; R. Zamana-Ramblas; S. Costa-Silva; N. Silvestre; T. Faita; L. B. Keid; R. M. Soares; C. F. Pessi; J. R. Sabbadini; M. F. Borges; et al. (Veterinary Research Communications, 2024)
In August 2021, two juvenile male Antarctic fur seals ( Arctocephalus gazella ) stranded in the southeastern Brazilian coast and were referred to rehabilitation centers. The animals presented increased body temperature, prostration, respiratory distress and despite treatment died. A necropsy following a standardized protocol was performed, and formalin-fixed tissues were processed for microscopic examination. Samples were screened for morbillivirus, herpesvirus, and Brucella spp. by molecular analyses (PCR, RT-PCR). Bacteriological culture was performed in samples collected from the lungs, trachea, and lymph nodes of both cases. The main histopathologic findings were of infectious nature, including multifocal necrotizing and fibrinous mixed interstitial pneumonia, bronchiolitis, and bronchitis, with intralesional myriad bacteria associated with vascular fibrinoid necrosis. Pseudomonas aeruginosa was isolated from tracheal and lung swabs of Case 1, and Klebsiella oxytoca was found in nostril swabs, tracheobronchial lymph nodes, and lung of Case 2. Gammaherpesvirus infection was detected in both cases, and the sequences retrieved were classified into the genus Percavirus . All tested samples were PCR-negative for Brucella spp. and morbillivirus. We hypothesize that the deficient immunological status in association with starvation predisposed the reactivation of herpesvirus and secondary bacterial co-infections. To the authors’ knowledge, this is the first molecular detection of herpesvirus in an Antarctic pinniped. These findings reinforce that Otariid gammaherpesvirus circulating in the Southern Hemisphere are likely endemic in the Arctocephalus genus. This report contributes to the current knowledge of health aspects affecting wild pinnipeds, especially in the poorly studied Antarctic species.

Phytochemical study of Magonia pubescens A. St.-Hil. and cytotoxicity of branches aqueous extract on breast cancer and leukemia cells - Acácio R. A. Moraes; Ezequias P. Siqueira; Markus Kohlhoff; Fernanda C. G. Evangelista; Adriano P. Sabino; Sidney A. Vieira Filho; Antônio F. C. Alcântara; Lucienir P. Duarte; Grasiely F. Sousa (Natural Product Research, 2024)

Freezing and thawing in Antarctica: characterization of antifreeze protein (AFP) producing microorganisms isolated from King George Island, Antarctica - J. C. Lopes; V. P. Veiga; B. Seminiuk; L. O. F. Santos; A. M. C. Luiz; C. A. Fernandes; C. T. Kinasz; V. H. Pellizari; R. T. D. Duarte (Brazilian Journal of Microbiology, 2024)

Assessing the euryhaline characteristics and metabolic responses of meagre (Argyrosomus regius) when reared under different salinities: Opportunities for aquaculture refinement - Marco F.L. Lemos; Cátia S.E. Silva; Lénia D. Rato; Alexandre F.S. Marques; Ricardo Passos; Irina A. Duarte; Bernardo Duarte; Vanessa F. Fonseca; Sara C. Novais (Aquaculture, 2024)

Antimicrobial prophylaxis in companion animal surgery: A scoping review for European Network for Optimization of Antimicrobial Therapy (ENOVAT) guidelines - T.M. Sørensen; K. Scahill; J. Espinel Ruperez; M. Olejnik; F. Swinbourne; D.R. Verwilghen; M.C. Nolff; S. Baines; C. Marques; A. Vilen; E.L. Duarte; M. Dias; et al. (The Veterinary Journal, 2024)

A common variant close to the “tripwire” linker region of NLRP1 contributes to severe COVID-19 - Vinicius N. C. Leal; Leandro M. Paulino; Raylane A. G. Cambui; Thiago G. Zupelli; Suemy M. Yamada; Leonardo A. T. Oliveira; Valéria de F. Dutra; Carolina B. Bub; Araci M. Sakashita; Ana Paula H. Yokoyama; José M. Kutner; Camila A. Vieira; et al. (Inflammation Research, 2023)

Fishery Closures, More Than Predator Release, Increased Persistence of Nearshore Fishes and Invertebrates to the Deepwater Horizon Oil Spill - Kiva L. Oken; Kenneth W. Able; Kim de Mutsert; F. Joel Fodrie; Paola C. López-Duarte; Charles W. Martin; Michael J. McCann; Jill A. Olin; Michael J. Polito; Brian J. Roberts; Olaf P. Jensen (Estuaries and Coasts, 2023)

Intrinsic and specific groundwater vulnerability determination as a pre-operational baseline assessment of an unconventional hydrocarbon industry - G. F. C. Lima; V. G. Ferreira; J. S. D. Lima; J. C. M. Duarte; A. C. Dufilho; C. A. de Carvalho Filho (International Journal of Environmental Science and Technology, 2023)

Norfloxacin prophylaxis effect on multidrug resistance in patients with cirrhosis and bacterial infections - Sebastián Marciano; Maria N. Gutierrez-Acevedo; Sabrina Barbero; Lorena del C. Notari; Marina Agozino; Jose L. Fernandez; Maria M. Anders; Nadia Grigera; Florencia Antinucci; Orlando F. Orozco Ganem; Maria D. Murga; Daniela Perez; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Rock n' Seeds: A database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation - Carlos A. Ordóñez‐Parra; Roberta L. C. Dayrell; Daniel Negreiros; Antônio C. S. Andrade; Letícia G. Andrade; Yasmine Antonini; Leilane C. Barreto; Fernanda de V. Barros; Vanessa da Cruz Carvalho; Blanca Auxiliadora Dugarte Corredor; Antônio Cláudio Davide; Alexandre A. Duarte; et al. (Ecology, 2023)
Advancing functional ecology depends fundamentally on the availability of data on reproductive traits, including those from tropical plants, which have been historically underrepresented in global trait databases. Although some valuable databases have been created recently, they are mainly restricted to temperate areas and vegetative traits such as leaf and wood traits. Here, we present Rock n' Seeds, a database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation, recognized as outstanding centers of diversity and endemism. Data were compiled through a systematic literature search, resulting in 103 publications from which seed functional traits were extracted. The database includes information on 16 functional traits for 383 taxa from 148 genera, 50 families, and 25 orders. These 16 traits include two dispersal, six production, four morphological, two biophysical, and two germination traits—the major axes of the seed ecological spectrum. The database also provides raw data for 48 germination experiments, for a total of 10,187 records for 281 taxa. Germination experiments in the database assessed the effect of a wide range of abiotic and biotic factors on germination and different dormancy‐breaking treatments. Notably, 8255 of these records include daily germination counts. This input will facilitate synthesizing germination data and using this database for a myriad of ecological questions. Given the variety of seed traits and the extensive germination information made available by this database, we expect it to be a valuable resource advancing comparative functional ecology and guiding seed‐based restoration and biodiversity conservation in tropical megadiverse ecosystems. There are no copyright restrictions on the data; please cite this paper when using the current data in publications; also the authors would appreciate notification of how the data are used in publications.

Transcriptome Analysis of Immune Response against Streptococcus agalactiae Infection in the Nile Tilapia GIFT Strain - Tao Zhou; Zhihua Fang; Daniel F. C. Duarte; Stefan A. Fernandes; Ying Lu; Jing Guo; Lang Gui; Liangbiao Chen (Fishes, 2022)
Streptococcus agalactiae (group B streptococcus, GBS), a broad-spectrum pathogen, causes great economic losses in fish aquaculture, especially the industry of tilapia. Until now, the knowledge of the immune response mechanism against S. agalactiae infection in tilapia has been limited. In the present study, the gill transcriptome of the tilapia from the GBS and the phosphate buffered saline (PBS) groups were sequenced. The transcriptomic analysis results presented the differentially expressed genes (DEGs) at different time points (DEGs number, 6 h: 2122, 9 h: 1851, 15 h: 1791, and 18 h: 2395) after GBS injection, and significantly enriched immune-related gene ontology (GO) terms such as the innate immune response. The significantly enriched immune pathways included the Toll-like receptor signaling pathway, the nucleotide oligomerization domain (NOD)-like receptor signaling pathway, the cytosolic-DNA sensing pathway, and the intestinal immune network for Immunoglobulin A (IgA) production. Most of the DEGs in Toll-like receptor signaling, NOD-like receptor signaling, and cytosolic-DNA sensing pathways presented upregulations at 18 h, which indicated that the innate immune pathways were activated. Two immune-related pathways (phagosome and cell adhesion molecules) were significantly enriched at all time points, suggesting that these two pathways might also play important roles in the immune response against the GBS infection. The results of HE staining showed that the gills of tilapia were damaged seriously at 9 h post-infection, which might be due to the possibility of pyroptosis resulting from the changes of DEGs in the NOD-like receptor signaling pathway. This study provided new insight into the mechanisms of gill damage in fish infected with S. agalactiae.

Different faces of cigarette butts, the most abundant beach litter worldwide - Maria Christina B. Araújo; Monica F. Costa; Jacqueline S. Silva-Cavalcanti; Armando C. Duarte; Vanessa Reis; Teresa A. Rocha-Santos; João Pinto da Costa; Violeta Girão (Environmental Science and Pollution Research, 2022)

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Global proteomic analysis of the follicular fluid from brown brocket deer (Mazama gouazoubira; Fisher, 1814) - Thais T. S. Souza; Maurício F. van Tilburg; Maria J. B. Bezerra; Luciana D. Rola; Leda M. C. Pereira; José M. B. Duarte; Maiana S. Chaves; Luciana M. Melo; Arlindo A. A. N. Moura; Vicente J. F. Freitas (European Journal of Wildlife Research, 2022)

Identification of potential new mosquito-associated viruses of adult Aedes aegypti mosquitoes from Tocantins state, Brazil - Matheus A. Duarte; Fabrício S. Campos; Osvaldo F. Araújo Neto; Leonardo A. Silva; Arthur B. Silva; Thalita C. Aguiar; Raissa N. Santos; Ueric J. B. Souza; Giselly B. Alves; Fernando L. Melo; Daniel M. P. Ardisson-Araujo; Raimundo W. S. Aguiar; et al. (Brazilian Journal of Microbiology, 2022)

A methanol extract and N,N-dimethyltryptamine from Psychotria viridis Ruiz & Pav. inhibit Zika virus infection in vitro - Thaís F. S. Moraes; Ariane C. Ferraz; Waleska S. da Cruz Nizer; Antônio H. Tótola; Débora B. S. Soares; Lucienir P. Duarte; Sidney A. Vieira-Filho; Cintia L. B. Magalhães; José C. de Magalhães (Archives of Virology, 2021)

Cecropia hololeuca : A new source of compounds with potential anti-inflammatory action - Emanuelle G. Machado; Oswaldo Cardoso; Nerilson M. Lima; Paloma E. Carvalho; Alice D. Barbosa; Guilherme F. S. Sobrinho; Jennifer F. Duarte; Laryssa R. Coelho; Pietra P. C. Soares; Ayane G. Orneles; Ana Carolina B. Santos; Kamila B. Santos; et al. (Natural Product Research, 2021)

Acarbose presents in vitro and in vivo antileishmanial activity against Leishmania infantum and is a promising therapeutic candidate against visceral leishmaniasis - Rafaella R. Costa; João A. Oliveira-da-Silva; Thiago A. R. Reis; Grasiele S. V. Tavares; Débora V. C. Mendonça; Camila S. Freitas; Daniela P. Lage; Vívian T. Martins; Luciana M. R. Antinarelli; Amanda S. Machado; Raquel S. Bandeira; Fernanda Ludolf; et al. (Medical Microbiology and Immunology, 2021)

In vitro and in silico studies of 8(17),12E,14-labdatrien-18-oic acid in airways smooth muscle relaxation: new molecular insights about its mechanism of action - Edilson B. Alencar Filho; Luciano A. A. Ribeiro; Thiego G. C. Carvalho; Fabrício S. Silva; Luiz Antonio M. S. Duarte-Filho; Euzébio G. Barbosa; Pedro M. N. Menezes; Josean F. Tavares; Marcelo S. da Silva; Bagnólia A. Silva (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Susan Lynn Williams: the Life of an Exceptional Scholar, Leader, and Friend (1951–2018) - William C. Dennison; Matthew E. S. Bracken; Maria Brown; John F. Bruno; James T. Carlton; Robert C. Carpenter; Tim J. B. Carruthers; Megan N. Dethier; Carlos M. Duarte; Thomas R. Fisher; James W. Fourqurean; Richard K. Grosberg; et al. (Estuaries and Coasts, 2021)
Susan Lynn Williams (1951–2018) was an exceptional marine ecologist whose research focused broadly on the ecology of benthic nearshore environments dominated by seagrasses, seaweeds, and coral reefs. She took an empirical approach founded in techniques of physiological ecology. Susan was committed to applying her research results to ocean management through outreach to decision-makers and resource managers. Susan’s career included research throughout the USA in tropical, temperate, and polar regions, but she specialized in tropical marine ecology. Susan’s scholarship, leadership, and friendship touched many people, leading to this multi-authored paper. Susan’s scholarship was multi-faceted, and she excelled in scientific discovery, integration of scientific results, application of science for conservation, and teaching, especially as a mentor to undergraduate and graduate students and postdoctoral scholars. Susan served in a variety of leadership positions throughout her career. She embodied all facets of leadership; leading by example, listening to others, committing to the “long haul,” maintaining trust, and creating a platform for all to shine. Susan was an important role model for women in science. Susan was also a loyal friend, maintaining friendships for many decades. Susan loved cooking and entertaining with friends. This paper provides an overview of the accomplishments of Susan in the broad categories of scholarship, leadership, and friendship.

Diversity of tomato-infecting begomoviruses and spatiotemporal dynamics of an endemic viral species of the Brazilian Atlantic rain forest biome - Macária F. Duarte; Maria E. N. Fonseca; Hélcio Costa; Niday A. N. Fernandes; Ailton Reis; Leonardo S. Boiteux; Rita C. Pereira-Carvalho (Virus Genes, 2021)

Effects of thermal shock on the survival and reproduction of Stratiolaelaps scimitus (Mesostigmata: Laelapidae) - Priscilla C. Gobbi; Juliano L. P. Duarte; Lucas R. da Silva; Dori E. Nava; Gustavo Sessa Fialho; Uemerson S. da Cunha; Adriane da F. Duarte (Experimental and Applied Acarology, 2020)

Assessing VIIRS capabilities to improve burned area mapping over the Brazilian Cerrado - Filippe L.M. Santos; Renata Libonati; Leonardo F. Peres; Allan A. Pereira; Luiza C. Narcizo; Julia A. Rodrigues; Duarte Oom; José M. C. Pereira; Wilfrid Schroeder; Alberto W. Setzer (International Journal of Remote Sensing, 2020)

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Phytochemical Characterization, Bioactivities Evaluation and Synergistic Effect of Arbutus unedo and Crataegus monogyna Extracts with Amphotericin B - Alexandra T. Coimbra; Ângelo F. S. Luís; Maria T. Batista; Susana M. P. Ferreira; Ana Paula C. Duarte (Current Microbiology, 2020)

Relationships Between Wildfires, Management Modalities of Community Areas, and Ownership Types in Pine Forests of Mainland Portugal - I. Skulska; I. Duarte; F. C. Rego; C. Montiel-Molina (Small-scale Forestry, 2020)

Comparative phylogeography of two free‐living cosmopolitan cyanobacteria: Insights on biogeographic and latitudinal distribution - Karine F. Ribeiro; Ana P. Ferrero; Leandro Duarte; Andreia C. Turchetto‐Zolet; Luciane O. Crossetti (Journal of Biogeography, 2020)
Aim Free‐living bacteria have long been assumed to have little biogeographic signature because of their high potential for passive dispersal. Raphidiopsis raciborskii and Microcystis aeruginosa are free‐living cosmopolitan cyanobacteria with a probable tropical origin, that frequently form toxic blooms and are considered invasive species in middle latitudes. Despite these similarities, their phylogeographic patterns have seldom been directly compared. Our aim was to reconstruct the phylogeographic histories of R. raciborskii and M. aeruginosa , in order to explore whether their current distributions could be attributed to the same biogeographic events. Location Global. Taxa Raphidiopsis raciborskii (Nostocales) and Microcystis aeruginosa (Chroococcales). Methods The phylogeography of these species was studied based on global genetic diversity patterns from a dataset of worldwide 16S rRNA gene sequences. Genetic diversity indices were measured globally and by latitude. Analyses based on distance matrices were performed to evaluate the correlation between genetic divergence, geographic distance and climatic conditions. Demographic history was investigated through neutrality tests and Bayesian Skyline Plot analysis. Results For both species, the genetic diversity is highest in tropical latitudes, and the data provided evidence of recent population expansions (in the last 2,500 years). R. raciborskii showed much lower genetic diversity than M. aeruginosa . A significant phylogeographic structure was found for R. raciborskii but not for M. aeruginosa . Climatic conditions had a significant influence on the genetic structure of both species, but this influence was stronger and varied according to latitude only for R. raciborskii . Main Conclusions Supporting the hypothesis of a tropical origin and recent dispersal to temperate habitats, both species had higher genetic diversity in tropical latitudes and showed evidence of recent population expansions. R. raciborskii populations showed a significant decline in genetic similarity with increasing geographic distance, indicating an interaction between drift and some dispersal limitation on its phylogeography. In contrast, M. aeruginosa seemed to have a high frequency of intercontinental dispersal. Finally, the particularities of each species, such as the ability to form akinetes in R. raciborskii and high genome plasticity and niche specialization in M. aeruginosa , may be associated with the lower genetic diversity of R. raciborskii when compared to M. aeruginosa .

Imines and lactones derived from friedelanes and their cytotoxic activity - Mariana G. Aguilar; Grasiely F. Sousa; Fernanda C. G. Evangelista; Adriano P. Sabino; Sidney A. Vieira Filho; Lucienir P. Duarte (Natural Product Research, 2020)

Evaluation of the cytotoxicity on breast cancer cell of extracts and compounds isolated from Hyptis pectinata (L.) poit - Fernanda R. Santana; Liany Luna-Dulcey; Víctor U. Antunes; Claudio F. Tormena; Marcia R. Cominetti; Marcelo C. Duarte; James A. da Silva (Natural Product Research, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Effects of leaf extracts of Protium spruceanum against adult and larval Rhipicephalus microplus - J. C. G. Figueiredo; Y. R. F. Nunes; Viviane de Oliveira Vasconcelos; S. R. Arruda; F. Morais-Costa; G. S. C. Santos; F. S. Alvez; E. R. Duarte (Experimental and Applied Acarology, 2019)

Supporting Spartina : Interdisciplinary perspective shows Spartina as a distinct solid genus - Alejandro Bortolus; Paul Adam; Janine B. Adams; Malika L. Ainouche; Debra Ayres; Mark D. Bertness; Tjeerd J. Bouma; John F. Bruno; Isabel Caçador; James T. Carlton; Jesus M. Castillo; Cesar S. B. Costa; et al. (Ecology, 2019)
In 2014, a DNA‐based phylogenetic study confirming the paraphyly of the grass subtribe Sporobolinae proposed the creation of a large monophyletic genus Sporobolus , including (among others) species previously included in the genera Spartina , Calamovilfa , and Sporobolus. Spartina species have contributed substantially (and continue contributing) to our knowledge in multiple disciplines, including ecology, evolutionary biology, molecular biology, biogeography, experimental ecology, biological invasions, environmental management, restoration ecology, history, economics, and sociology. There is no rationale so compelling to subsume the name Spartina as a subgenus that could rival the striking, global iconic history and use of the name Spartina for over 200 yr. We do not agree with the subjective arguments underlying the proposal to change Spartina to Sporobolus . We understand the importance of both the objective phylogenetic insights and of the subjective formalized nomenclature and hope that by opening this debate we will encourage positive feedback that will strengthen taxonomic decisions with an interdisciplinary perspective. We consider that the strongly distinct, monophyletic clade Spartina should simply and efficiently be treated as the genus Spartina .

Evaluation of hydration of cement pastes containing high volume of mineral additions - M. A. S. Anjos; R. Reis; A. Camões; F. Duarte; C. Jesus (European Journal of Environmental and Civil Engineering, 2019)

Mitochondria and the Brain: Bioenergetics and Beyond - Pascale Belenguer; João M. N. Duarte; Patrícia F. Schuck; Gustavo C. Ferreira (Neurotoxicity Research, 2019)

Global challenges for seagrass conservation - Richard K. F. Unsworth; Len J. McKenzie; Catherine J. Collier; Leanne C. Cullen-Unsworth; Carlos M. Duarte; Johan S. Eklöf; Jessie C. Jarvis; Benjamin L. Jones; Lina M. Nordlund (Ambio, 2019)

Toward a Coordinated Global Observing System for Seagrasses and Marine Macroalgae - J. Emmett Duffy; Lisandro Benedetti-Cecchi; Joaquin Trinanes; Frank E. Muller-Karger; Rohani Ambo-Rappe; Christoffer Boström; Alejandro H. Buschmann; Jarrett Byrnes; Robert G. Coles; Joel Creed; Leanne C. Cullen-Unsworth; Guillermo Diaz-Pulido; et al. (Frontiers in Marine Science, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

First-order effects of fire and prolonged-drought effects on an undescribed semi-aquatic turtle in Atlantic rainforest in southeastern Brazil - Jane C. F. Oliveira; Thiago Marcial Castro; Thiago Silva-Soares; Carlos Frederico Duarte Rocha (Journal of Coastal Conservation, 2019)

Biological treatment of vinasse with yeast and simultaneous production of single-cell protein for feed supplementation - K. C. dos Reis; J. M. Coimbra; W. F. Duarte; R. F. Schwan; C. F. Silva (International Journal of Environmental Science and Technology, 2019)

Aged rats are more vulnerable than adolescents to “ecstasy”-induced toxicity - R. Feio-Azevedo; V. M. Costa; D. J. Barbosa; A. Teixeira-Gomes; I. Pita; S. Gomes; F. C. Pereira; M. Duarte-Araújo; J. A. Duarte; F. Marques; E. Fernandes; M. L. Bastos; et al. (Archives of Toxicology, 2018)

Effects of a nanoemulsion with Copaifera officinalis oleoresin against monogenean parasites of Colossoma macropomum: A Neotropical Serrasalmidae - D S S Valentim; J L Duarte; A E M F M Oliveira; R A S Cruz; J C T Carvalho; C Solans; C P Fernandes; M Tavares‐Dias (Journal of Fish Diseases, 2018)
Monogeneans are ectoparasites that may cause losses in production and productivity in the aquaculture of Colossoma macropomum . Chemotherapeutics used in aquaculture usually have major adverse effects on fish; hence, the use of essential oils has been considered advantageous, but these are not soluble in water. Thus, the use of nanostructures to enhance water solubility of compounds and improve bioactivity may be very promising. This study investigated the antiparasitic activity of nanoemulsion prepared with Copaifera officinalis oleoresin (50, 100, 150, 200 and 300 mg/L), against monogenean parasites from the gills of C. macropomum . The particle size distribution and zeta potential suggested that a potentially kinetic stable system was generated. The nanoemulsion from C. officinalis oleoresin achieved high efficacy (100%) at low concentrations (200 and 300 mg/L) after 15 min of exposure. This was the first time that a nanoemulsion was generated from C. officinalis oleoresin using a solvent‐free, non‐heating and low‐energy method. Moreover, this was the first time that an antiparasitic against monogeneans on fish gills, based on nanoemulsion of C. officinalis oleoresin, was tested.

Detection of the antiviral activity of epicatechin isolated from Salacia crassifolia (Celastraceae) against Mayaro virus based on protein C homology modelling and virtual screening - P. G. Ferreira; A. C. Ferraz; J. E. Figueiredo; C. F. Lima; V. G. Rodrigues; A. G. Taranto; J. M. S. Ferreira; G. C. Brandão; S. A. Vieira-Filho; L. P. Duarte; C. L. de Brito Magalhães; J. C. de Magalhães (Archives of Virology, 2018)

β-(1→6)-d-glucan secreted during the optimised production of exopolysaccharides by Paecilomyces variotii has immunostimulatory activity - Erica F. Osaku; Rafael A. Menolli; Claudia R. L. de M. Costa; Fernando Henrique G. Tessaro; Renan H. de Melo; Alex E. do Amaral; Péricles A. D. Duarte; Arquimedes Paixão de Santana Filho; Andrea Caroline Ruthes; José Luis da C. Silva; Rosiane G. Mello (Antonie van Leeuwenhoek, 2018)

Nanoemulsion from essential oil of Pterodon emarginatus (Fabaceae) shows in vitro efficacy against monogeneans of Colossoma macropomum (Pisces: Serrasalmidae) - D S S Valentim; J L Duarte; A E M F M Oliveira; R A S Cruz; J C T Carvalho; E C Conceição; C P Fernandes; M Tavares‐Dias (Journal of Fish Diseases, 2018)
Outbreaks of diseases pose a major threat to sustainable aquaculture development worldwide. Application of herbal products to combat parasitic diseases provides an alternative approach for sustainable aquaculture. This study investigated the in vitro antiparasitic effects of an oil‐in‐water nanoemulsion prepared using the essential oil from Pterodon emarginatus , against monogeneans infesting Colossoma macropomum . Gill arches from C. macropomum (47.6 ± 14.5 g and 13.5 ± 1.4 cm) that were naturally parasitized by Anacanthorus spathulatus , Notozothecium janauachensis and Mymarothecium boegeri were immersed in different dispersions of the P. emarginatus nanoemulsions (0, 50, 100, 200, 400 and 600 mg/L). The major compounds presented in the essential oil of P. emarginatus were β‐elemene, β‐caryophyllene and α‐humulene. Characterization of these nanoemulsions showed that they have a small mean droplet size and low polydispersity index, which is concordant with stable systems. In this in vitro trial, the P. emarginatus nanoemulsion concentrations of 100, 200, 400 and 600 mg/L presented 100% helminthic efficacy against monogeneans of the gills of C. macropomum . The highest two concentrations used (400 and 600 mg/L) were seen to immobilize the parasites after only 15 min. Therefore, it would be worthwhile testing these concentrations in therapeutic baths against monogeneans of C. macropomum .

New Tools to Identify the Location of Seagrass Meadows: Marine Grazers as Habitat Indicators - Graeme C. Hays; Teresa Alcoverro; Marjolijn J. A. Christianen; Carlos M. Duarte; Mark Hamann; Peter I. Macreadie; Helene D. Marsh; Michael A. Rasheed; Michele Thums; Richard K. F. Unsworth; Paul H. York; Nicole Esteban (Frontiers in Marine Science, 2018)

ATLANTIC MAMMAL TRAITS : a data set of morphological traits of mammals in the Atlantic Forest of South America - Fernando Gonçalves; Ricardo S. Bovendorp; Gabrielle Beca; Carolina Bello; Raul Costa‐Pereira; Renata L. Muylaert; Raisa R. Rodarte; Nacho Villar; Rafael Souza; Maurício E. Graipel; Jorge J. Cherem; Deborah Faria; et al. (Ecology, 2018)
Measures of traits are the basis of functional biological diversity. Numerous works consider mean species‐level measures of traits while ignoring individual variance within species. However, there is a large amount of variation within species and it is increasingly apparent that it is important to consider trait variation not only between species, but also within species. Mammals are an interesting group for investigating trait‐based approaches because they play diverse and important ecological functions (e.g., pollination, seed dispersal, predation, grazing) that are correlated with functional traits. Here we compile a data set comprising morphological and life history information of 279 mammal species from 39,850 individuals of 388 populations ranging from −5.83 to −29.75 decimal degrees of latitude and −34.82 to −56.73 decimal degrees of longitude in the Atlantic forest of South America. We present trait information from 16,840 individuals of 181 species of non‐volant mammals (Rodentia, Didelphimorphia, Carnivora, Primates, Cingulata, Artiodactyla, Pilosa, Lagomorpha, Perissodactyla) and from 23,010 individuals of 98 species of volant mammals (Chiroptera). The traits reported include body mass, age, sex, reproductive stage, as well as the geographic coordinates of sampling for all taxa. Moreover, we gathered information on forearm length for bats and body length and tail length for rodents and marsupials. No copyright restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Diet and body shape changes of pāroko Kelloggella disalvoi (Gobiidae) from intertidal pools of Easter Island - J. Vera‐Duarte; C. A. Bustos; M. F. Landaeta (Journal of Fish Biology, 2017)
This study assesses seasonal variation in the morphology and diet of juveniles and adults of the Easter Island endemic goby Kelloggella disalvoi from intertidal pools during September–October 2015 (spring) and June–July 2016 (winter), utilizing geometric morphometric and gut‐content analyses. A set of 16 landmarks was digitized in 128 individuals. Shape changes related to size changes ( i.e . allometry) were low (18·6%) and were seasonally similar. Body shape changes were mainly dorsoventral (44·2% of variance) and comprised posteroventral displacement of the premaxilla and bending of the body. The latter included vertical displacement of the anterior portion of the first and second dorsal fins and the entire base of the caudal fin. Diets mainly comprised developmental stages of harpacticoid copepods (from eggs to adults), ostracods, isopods, gastropods and bivalves. Also, trophic niche breadth remained constant throughout development and did not vary between seasons. Nonetheless, significant dietary differences were detected in specimens collected during spring (main prey items: harpacticoid copepods and copepod eggs) and winter (harpacticoid copepods and copepod nauplii). Finally, there was weak but significant covariation between diet and morphology: molluscivores were characterized by having an inferior mouth gape, whereas planktivores had an anteriorly directed premaxilla.

ATLANTIC ‐ CAMTRAPS : a dataset of medium and large terrestrial mammal communities in the Atlantic Forest of South America - Fernando Lima; Gabrielle Beca; Renata L. Muylaert; Clinton N. Jenkins; Miriam L. L. Perilli; Ana Maria O. Paschoal; Rodrigo L. Massara; Adriano P. Paglia; Adriano G. Chiarello; Maurício E. Graipel; Jorge J. Cherem; André L. Regolin; et al. (Ecology, 2017)
Our understanding of mammal ecology has always been hindered by the difficulties of observing species in closed tropical forests. Camera trapping has become a major advance for monitoring terrestrial mammals in biodiversity rich ecosystems. Here we compiled one of the largest datasets of inventories of terrestrial mammal communities for the Neotropical region based on camera trapping studies. The dataset comprises 170 surveys of medium to large terrestrial mammals using camera traps conducted in 144 areas by 74 studies, covering six vegetation types of tropical and subtropical Atlantic Forest of South America (Brazil and Argentina), and present data on species composition and richness. The complete dataset comprises 53,438 independent records of 83 species of mammals, includes 10 species of marsupials, 15 rodents, 20 carnivores, eight ungulates and six armadillos. Species richness averaged 13 species (±6.07 SD ) per site. Only six species occurred in more than 50% of the sites: the domestic dog Canis familiaris , crab‐eating fox Cerdocyon thous , tayra Eira barbara , south American coati Nasua nasua , crab‐eating raccoon Procyon cancrivorus and the nine‐banded armadillo Dasypus novemcinctus . The information contained in this dataset can be used to understand macroecological patterns of biodiversity, community, and population structure, but also to evaluate the ecological consequences of fragmentation, defaunation, and trophic interactions.

Guanosine Exerts Neuroprotective Effect in an Experimental Model of Acute Ammonia Intoxication - G. F. Cittolin-Santos; A. M. de Assis; P. A. Guazzelli; L. G. Paniz; J. S. da Silva; M. E. Calcagnotto; G. Hansel; K. C. Zenki; E. Kalinine; M. M. Duarte; D. O. Souza (Molecular Neurobiology, 2017)

Synthesis and antileishmanial activity of 1,3-bis(aryloxy)propan-2-amines - Stefânia N. Lavorato; Mariana C. Duarte; Daniela P. Lage; Carlos A. P. Tavares; Eduardo A. F. Coelho; Ricardo J. Alves (Medicinal Chemistry Research, 2017)

Investigating essential and toxic elements in Antarctic macroalgae using a green analytical method - Rochele S. Picoloto; Rodrigo M. Pereira; Vanize C. Costa; Carla A. Hartwig; Claudio M. P. Pereira; Pio Colepicolo; Fabio A. Duarte; Marcia F. Mesko (Journal of Applied Phycology, 2017)

Genotoxicity of citrate-coated silver nanoparticles to human keratinocytes assessed by the comet assay and cytokinesis blocked micronucleus assay - V. Bastos; I. F. Duarte; C. Santos; H. Oliveira (Environmental Science and Pollution Research, 2017)

Music supported therapy promotes motor plasticity in individuals with chronic stroke - P. Ripollés; N. Rojo; J. Grau-Sánchez; J. L. Amengual; E. Càmara; J. Marco-Pallarés; M. Juncadella; L. Vaquero; F. Rubio; E. Duarte; C. Garrido; E. Altenmüller; et al. (Brain Imaging and Behavior, 2016)

Prevalence of the genus Cladosporium on the integument of leaf-cutting ants characterized by 454 pyrosequencing - A. P. M. Duarte; M. Ferro; A. Rodrigues; M. Bacci; N. S. Nagamoto; L. C. Forti; F. C. Pagnocca (Antonie van Leeuwenhoek, 2016)

Cytokines profile and its correlation with endothelial damage and oxidative stress in patients with type 1 diabetes mellitus and nephropathy - Rodrigo M. C. Pestana; Caroline P. Domingueti; Rita C. F. Duarte; Rodrigo B. Fóscolo; Janice S. Reis; Ana Maria S. Rodrigues; Laís B. Martins; Lirlândia P. Sousa; Daniela P. Lage; Cláudia N. Ferreira; Adaliene V. M. Ferreira; Ana P. Fernandes; et al. (Immunologic Research, 2016)

Modulation of aquaporins 3 and 9 after exposure of ovine ovarian tissue to cryoprotectants followed by in vitro culture - A. D. Sales; A. B. G. Duarte; R. R. Santos; K. A. Alves; L. F. Lima; G. Q. Rodrigues; I. R. Brito; C. H. Lobo; J. B. Bruno; Y. Locatelli; J. R. Figueiredo; A. P. R. Rodrigues (Cell and Tissue Research, 2016)

Advantages and limitations of chemical extraction tests to predict mercury soil-plant transfer in soil risk evaluations - R. J. R. Monteiro; S. M. Rodrigues; N. Cruz; B. Henriques; A. C. Duarte; P. F. A. M. Römkens; E. Pereira (Environmental Science and Pollution Research, 2016)

Photocatalytic Treatment of Olive Oil Mill Wastewater Using TiO2 and Fe2O3 Nanomaterials - V. Nogueira; I. Lopes; T. A. P. Rocha-Santos; F. Gonçalves; A. C. Duarte; R. Pereira (Water, Air, & Soil Pollution, 2016)

Rhizopus arrhizus and Fusarium solani Concomitant Infection in an Immunocompromised Host - João N. de Almeida Júnior; Karim Y. Ibrahim; Gilda M. B. Del Negro; Evandro D. Bezerra; Amaro N. Duarte Neto; Marjorie V. Batista; Rinaldo F. Siciliano; Mauro C. Giudice; Adriana L. Motta; Flávia Rossi; Ligia C. Pierrotti; Maristela P. Freire; et al. (Mycopathologia, 2016)

Antileishmanial activity of compounds produced by endophytic fungi derived from medicinal plant Vernonia polyanthes and their potential as source of bioactive substances - Adriana M. do Nascimento; Mateus Gonçalves Soares; Fernanda K. V. da Silva Torchelsen; Jorge A. Viana de Araujo; Paula S. Lage; Mariana C. Duarte; Pedro H. R. Andrade; Tatiana G. Ribeiro; Eduardo A. F. Coelho; Andréa M. do Nascimento (World Journal of Microbiology and Biotechnology, 2015)

Fish Assemblages in Louisiana Salt Marshes: Effects of the Macondo Oil Spill - Kenneth W. Able; Paola C. López-Duarte; F. Joel Fodrie; Olaf P. Jensen; Charles W. Martin; Brian J. Roberts; Jessica Valenti; Kathleen O’Connor; Shanina C. Halbert (Estuaries and Coasts, 2015)

Assessing the ecotoxicity of metal nano-oxides with potential for wastewater treatment - V. Nogueira; I. Lopes; T. A. P. Rocha-Santos; M. G. Rasteiro; N. Abrantes; F. Gonçalves; A. M. V. M. Soares; A. C. Duarte; R. Pereira (Environmental Science and Pollution Research, 2015)

Recurrent patterns of phylogenetic habitat filtering in woody plant communities across phytogeographically distinct grassland-forest ecotones - V. J. Debastiani; S. C. Muller; J. M. Oliveira; F. S. Rocha; M. C. Sestren-Bastos; L. D. S. Duarte (Community Ecology, 2015)

Catalog of total excitation–emission and total synchronous fluorescence maps with synchronous fluorescence spectra of homologated fluorescent pesticides in large use in Morocco: development of a spectrometric low cost and direct analysis as an alert method in case of massive contamination of soils and waters by fluorescent pesticides - S. Foudeil; H. Hassoun; T. Lamhasni; S. Ait Lyazidi; F. Benyaich; M. Haddad; M. Choukrad; A. Boughdad; M. Bounakhla; H. Bounouira; R. M. B. O. Duarte; A. Cachada; et al. (Environmental Science and Pollution Research, 2015)

A new species of the oligotrophic genus Ochroconis (Sympoventuriaceae) - K. Samerpitak; A. P. M. Duarte; D. Attili-Angelis; F. C. Pagnocca; G. Heinrichs; A. J. M. M. Rijs; A. Alfjorden; A. H. G. Gerrits van den Ende; S. B. J. Menken; G. S. de Hoog (Mycological Progress, 2015)

Journal of coastal conservation: a review on the anurofauna of Brazil’s sandy coastal plains. How much do we know about it? - Jane C. F. Oliveira; Carlos Frederico Duarte Rocha (Journal of Coastal Conservation, 2015)

Geochemistry, mineralogy, solid-phase fractionation and oral bioaccessibility of lead in urban soils of Lisbon - A. P. Reis; C. Patinha; J. Wragg; A. C. Dias; M. Cave; A. J. Sousa; C. Costa; A. Cachada; E. Ferreira da Silva; F. Rocha; A. Duarte (Environmental Geochemistry and Health, 2014)

Diazoxide Attenuates Autoimmune Encephalomyelitis and Modulates Lymphocyte Proliferation and Dendritic Cell Functionality - N. Virgili; P. Mancera; C. Chanvillard; A. Wegner; B. Wappenhans; M. J. Rodríguez; C. Infante-Duarte; J. F. Espinosa-Parrilla; M. Pugliese (Journal of Neuroimmune Pharmacology, 2014)

Leaf-cutting ants: an unexpected microenvironment holding human opportunistic black fungi - A. P. M. Duarte; D. Attili-Angelis; N. C. Baron; L. C. Forti; F. C. Pagnocca (Antonie van Leeuwenhoek, 2014)

Blowflies (Diptera, Calliphoridae) Associated with Pig Carcasses in a Caatinga Area, Northeastern Brazil - A C F Alves; W E Santos; R C A P Farias; A J Creão-Duarte (Neotropical Entomology, 2014)

Climate effects on amphibian distributions depend on phylogenetic resolution and the biogeographical history of taxa - L. D. S. Duarte; C. Both; V. J. Debastiani; M. B. Carlucci; L. O. Gonçalves; L. Cappelatti; G. D. S. Seger; V. A. G. Bastazini; F. T. Brum; E. V. Salengue; J. S. Bernardo‐Silva (Global Ecology and Biogeography, 2014)
Aim Disentangling the effects of climate and historical factors on biodiversity distribution remains a challenge for biogeographers. Here, we provide an analytical framework to discriminate the contributions of contemporary climate and the biogeographical history of taxa to the geographical distributions of phylogenetic lineages. Furthermore, we evaluate the constraint that the biogeographical history of clades exerts on the association between climate and clade distribution, i.e. the historical legacy of climatic effects. As a case study, we analysed the distributions of amphibian lineages across the A mericas. Location The A mericas. Methods We tallied the number of amphibian species per genus in each of 262 ecoregions. Each ecoregion was described by the composition of phylogenetic lineages using phylogenetic fuzzy weighting. The composition of amphibian genera and phylogenetic clades represented the distributions of shallow and deep phylogenetic nodes, respectively. We characterized each ecoregion by the biogeographical history of amphibian taxa and its current climate, whose influences on shallow and deep phylogenetic nodes were analysed using variation partitioning analysis. Results The association between climate and the distributions of deep phylogenetic nodes showed a strong historical legacy, although the distribution of amphibian genera was mostly associated with climate. Hyloidea were associated with a G ondwanan origin and higher annual mean temperatures, whereas other clades (e.g. C audata) were related to a L aurasian origin and higher temperature seasonality. Microhylidae were related to occurrence in the E arly J urassic in G ondwana and recent occurrence in the N eotropics. Main conclusions Biogeographical patterns can be thought of as the net outcome of evolutionary, historical and ecological processes. Although temperature is likely to affect the ecology of amphibians, the effects of climate on the distributions of deep phylogenetic nodes were strongly constrained by the biogeographical history of clades. Nevertheless, local, climatically driven processes are likely to influence the distributions of shallow phylogenetic nodes. The historical biogeography of clades might help to explain the interplay between evolutionary and environmental processes in determining assembly patterns found elsewhere.

Algistatic effect of a quinonamethide triterpene on Microcystis novacekii - Fernando C. Silva; Fernanda A. F. Guedes; Maione W. Franco; Francisco A. R. Barbosa; Camila A. Marra; Lucienir P. Duarte; Grácia D. F. Silva; Sidney A. Vieira-Filho (Journal of Applied Phycology, 2013)

Taxonomic assessment and enzymes production by yeasts isolated from marine and terrestrial Antarctic samples - A. W. F. Duarte; I. Dayo-Owoyemi; F. S. Nobre; F. C. Pagnocca; L. C. S. Chaud; A. Pessoa; M. G. A. Felipe; L. D. Sette (Extremophiles, 2013)

Decomposition and nutrient release in leaves of Atlantic Rainforest tree species used in agroforestry systems - Edivânia M. G. Duarte; Irene M. Cardoso; Thomas Stijnen; Maria Alice F. C. Mendonça; Marino S. Coelho; Reinaldo B. Cantarutti; Thomas W. Kuyper; Ecila M. A. Villani; Eduardo S. Mendonça (Agroforestry Systems, 2013)

Derivation of soil to plant transfer functions for metals and metalloids: impact of contaminant’s availability - S. M. Rodrigues; E. Pereira; A. C. Duarte; P. F. A. M. Römkens (Plant and Soil, 2012)

Hematological indices and activity of NTPDase and cholinesterase enzymes in rats exposed to cadmium and treated with N-acetylcysteine - Jamile F. Gonçalves; Marta M. M. F. Duarte; Amanda M. Fiorenza; Roselia M. Spanevello; Cinthia M. Mazzanti; Roberta Schmatz; Margarete D. Bagatini; Fabiane G. Antes; Pauline Costa; Fátima H. Abdalla; Valderi L. Dressler; Vera M. Morsch; et al. (BioMetals, 2012)

Pesticide application to agricultural fields: effects on the reproduction and avoidance behaviour of Folsomia candida and Eisenia andrei - M. J. G. Santos; M. F. L. Ferreira; A. Cachada; A. C. Duarte; J. P. Sousa (Ecotoxicology, 2012)

Biomass-Derived Inhibitors of Holocellulases - Gilvan C. Duarte; Leonora Rios S. Moreira; Paula Marcela D. Jaramillo; Edivaldo Ximenes F. Filho (BioEnergy Research, 2012)

Hg transfer from contaminated soils to plants and animals - S. M. Rodrigues; B. Henriques; A. T. Reis; A. C. Duarte; E. Pereira; P. F. A. M. Römkens (Environmental Chemistry Letters, 2012)

Kinetics of Mercury Bioaccumulation in the Polychaete Hediste diversicolor and in the Bivalve Scrobicularia plana, Through a Dietary Exposure Pathway - Patricia G. Cardoso; Eduarda Pereira; Tiago F. Grilo; Armando C. Duarte; Miguel A. Pardal (Water, Air, & Soil Pollution, 2012)

Early-life environmental intervention may increase the number of neurons, astrocytes, and cellular proliferation in the hippocampus of rats - Elisa C. Winkelmann-Duarte; Camila B. Padilha-Hoffmann; Daniel F. Martins; Artur F. S. Schuh; Marilda C. Fernandes; Ricardo Santin; Suelen Merlo; Gilberto L. Sanvitto; Aldo B. Lucion (Experimental Brain Research, 2011)

Vascular endothelial growth factor-A165 (VEGF-A165) stimulates the in vitro development and oocyte competence of goat preantral follicles - V. R. Araújo; G. M. Silva; A. B. G. Duarte; D. M. Magalhães; A. P. Almeida; R. F. B. Gonçalves; J. B. Bruno; T. F. P. Silva; C. C. Campello; A. P. R. Rodrigues; J. R. Figueiredo (Cell and Tissue Research, 2011)

TRY – a global database of plant traits - J. KATTGE; S. DÍAZ; S. LAVOREL; I. C. PRENTICE; P. LEADLEY; G. BÖNISCH; E. GARNIER; M. WESTOBY; P. B. REICH; I. J. WRIGHT; J. H. C. CORNELISSEN; C. VIOLLE; et al. (Global Change Biology, 2011)
Plant traits – the morphological, anatomical, physiological, biochemical and phenological characteristics of plants and their organs – determine how primary producers respond to environmental factors, affect other trophic levels, influence ecosystem processes and services and provide a link from species richness to ecosystem functional diversity. Trait data thus represent the raw material for a wide range of research from evolutionary biology, community and functional ecology to biogeography. Here we present the global database initiative named TRY, which has united a wide range of the plant trait research community worldwide and gained an unprecedented buy‐in of trait data: so far 93 trait databases have been contributed. The data repository currently contains almost three million trait entries for 69 000 out of the world's 300 000 plant species, with a focus on 52 groups of traits characterizing the vegetative and regeneration stages of the plant life cycle, including growth, dispersal, establishment and persistence. A first data analysis shows that most plant traits are approximately log‐normally distributed, with widely differing ranges of variation across traits. Most trait variation is between species (interspecific), but significant intraspecific variation is also documented, up to 40% of the overall variation. Plant functional types (PFTs), as commonly used in vegetation models, capture a substantial fraction of the observed variation – but for several traits most variation occurs within PFTs, up to 75% of the overall variation. In the context of vegetation models these traits would better be represented by state variables rather than fixed parameter values. The improved availability of plant trait data in the unified global database is expected to support a paradigm shift from species to trait‐based ecology, offer new opportunities for synthetic plant trait research and enable a more realistic and empirically grounded representation of terrestrial vegetation in Earth system models.

The small nuclear ribonucleoprotein U1A interacts with NS5 from yellow fever virus - Roberta V. M. Bronzoni; Maria C. F. S. Madrid; Danilo V. B. Duarte; Vanessa O. A. Pellegrini; Carolina C. Pacca; Ana C. V. Carmo; Cleslei F. Zanelli; Sandro R. Valentini; Carolina Santacruz-Pérez; João A. R. G. Barbosa; Carol S. Lutz; Paula Rahal; et al. (Archives of Virology, 2011)

Genetic similarity among genotypes of sugarcane estimated by SSR and coefficient of parentage - L. S. C. Duarte Filho; P. P. Silva; J. M. Santos; G. V. S. Barbosa; C. E. Ramalho-Neto; L. Soares; J. C. F. Andrade; C. Almeida (Sugar Tech, 2010)

An NMR structural study of nickel-substituted rubredoxin - Brian J. Goodfellow; Iven C. N. Duarte; Anjos L. Macedo; Brian F. Volkman; Sofia G. Nunes; I. Moura; John L. Markley; José J. G. Moura (JBIC Journal of Biological Inorganic Chemistry, 2010)

Foliar application of potassium silicate reduces the intensity of soybean rust - F. A. Rodrigues; H. S. S. Duarte; G. P. Domiciano; C. A. Souza; G. H. Korndörfer; L. Zambolim (Australasian Plant Pathology, 2009)

Metabolic activity interferometer: description and calibration of an interferometric method to measure growth of mycobacteria - R. R. P. Machado; E. S. Lima Filho; D. F. Jardim; M. A. A. Ferreira; C. G. de Faria; R. S. Duarte; B. Lesche (European Biophysics Journal, 2008)

New developments in understanding and treating neuroinflammation - C. Infante-Duarte; S. Waiczies; J. Wuerfel; F. Zipp (Journal of Molecular Medicine, 2008)

Evaluation of the microbial diversity in a horizontal-flow anaerobic immobilized biomass reactor treating linear alkylbenzene sulfonate - I. C. S. Duarte; L. L. Oliveira; N. K. D. Saavedra; F. Fantinatti-Garboggini; V. M. Oliveira; M. B. A. Varesche (Biodegradation, 2008)

First assessment of microbial diversity in faecal microflora of Eurasian otter (Lutra lutra Linnaeus, 1758) in Portugal - M. Oliveira; T. Sales-Luís; A. Duarte; S. F. Nunes; C. Carneiro; T. Tenreiro; R. Tenreiro; M. Santos-Reis; L. Tavares; C. L. Vilela (European Journal of Wildlife Research, 2008)

Standardizing methods to address clonality in population studies - S. ARNAUD‐HAOND; C. M. DUARTE; F. ALBERTO; E. A. SERRÃO (Molecular Ecology, 2007)
Although clonal species are dominant in many habitats, from unicellular organisms to plants and animals, ecological and particularly evolutionary studies on clonal species have been strongly limited by the difficulty in assessing the number, size and longevity of genetic individuals within a population. The development of molecular markers has allowed progress in this area, and although allozymes remain of limited use due to their typically low level of polymorphism, more polymorphic markers have been discovered during the last decades, supplying powerful tools to overcome the problem of clonality assessment. However, population genetics studies on clonal organisms lack a standardized framework to assess clonality, and to adapt conventional data analyses to account for the potential bias due to the possible replication of the same individuals in the sampling. Moreover, existing studies used a variety of indices to describe clonal diversity and structure such that comparison among studies is difficult at best. We emphasize the need for standardizing studies on clonal organisms, and particularly on clonal plants, in order to clarify the way clonality is taken into account in sampling designs and data analysis, and to allow further comparison of results reported in distinct studies. In order to provide a first step towards a standardized framework to address clonality in population studies, we review, on the basis of a thorough revision of the literature on population structure of clonal plants and of a complementary revision on other clonal organisms, the indices and statistics used so far to estimate genotypic or clonal diversity and to describe clonal structure in plants. We examine their advantages and weaknesses as well as various conceptual issues associated with statistical analyses of population genetics data on clonal organisms. We do so by testing them on results from simulations, as well as on two empirical data sets of microsatellites of the seagrasses Posidonia oceanica and Cymodocea nodosa . Finally, we also propose a selection of new indices and methods to estimate clonal diversity and describe clonal structure in a way that should facilitate comparison between future studies on clonal plants, most of which may be of interest for clonal organisms in general.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Plumbing the Global Carbon Cycle: Integrating Inland Waters into the Terrestrial Carbon Budget - J. J. Cole; Y. T. Prairie; N. F. Caraco; W. H. McDowell; L. J. Tranvik; R. G. Striegl; C. M. Duarte; P. Kortelainen; J. A. Downing; J. J. Middelburg; J. Melack (Ecosystems, 2007)

Molecular characterization and antimicrobial activity of endophytic fungi from coffee plants - L. D. Sette; M. R. Z. Passarini; C. Delarmelina; F. Salati; M. C. T. Duarte (World Journal of Microbiology and Biotechnology, 2006)

Physiological synecology of tree species in relation to geographic distribution and ecophysiological parameters at the Atlantic forest periphery in Brazil: an overview - F. R. Scarano; H. M. Duarte; A. C. Franco; A. Geβler; E. A. de Mattos; H. Rennenberg; U. Lüttge (Trees, 2006)

Ecophysiology of selected tree species in different plant communities at the periphery of the Atlantic Forest of SE-Brazil II. Spatial and ontogenetic dynamics in Andira legalis, a deciduous legume tree - A. Geβler; H. M. Duarte; A. C. Franco; U. Lüttge; E. A. de Mattos; M. Nahm; F. R. Scarano; H. L. T. Zaluar; H. Rennenberg (Trees, 2005)

Ecophysiology of selected tree species in different plant communities at the periphery of the Atlantic Forest of SE Brazil I. Performance of three different species of Clusia in an array of plant communities - F. R. Scarano; H. M. Duarte; A. C. Franco; A. Geβler; E. A. de Mattos; M. Nahm; H. Rennenberg; H. L. T. Zaluar; U. Lüttge (Trees, 2005)

Ecophysiology of selected tree species in different plant communities at the periphery of the Atlantic Forest of SE—Brazil III. Three legume trees in a semi-deciduous dry forest - A. Geßler; H. M. Duarte; A. C. Franco; U. Lüttge; E. A. de Mattos; M. Nahm; P. J. F. P. Rodrigues; F. R. Scarano; H. Rennenberg (Trees, 2005)

Physiological synecology of tree species in relation to geographic distribution and ecophysiological parameters at the Atlantic forest periphery in Brazil: an overview - F. R. Scarano; H. M. Duarte; A. C. Franco; A. Geβler; E. A. de Mattos; H. Rennenberg; U. Lüttge (Trees, 2005)

In situ measurements of carbon and nitrogen distribution and composition, photochemical efficiency and stable isotope ratios in Araucaria angustifolia - A. C. Franco; H. M. Duarte; A. Geβler; E. A. de Mattos; M. Nahm; H. Rennenberg; K. T. Ribeiro; F. R. Scarano; U. Lüttge (Trees, 2005)

A case of eumycetoma due to Madurella grisea in northern Brazil - Raquel Vilela; Olga M. V. Duarte; Carlos A. Rosa; Joao G. F. Castro; Sandra Lyon; Roberta L. Motta; Ana C. L. Moura (Mycopathologia, 2004)

Ca2+ and the bacterial peroxidases: the cytochrome c peroxidase from Pseudomonas stutzeri - Cristina G. Timóteo; Pedro Tavares; Celia F. Goodhew; Luís C. Duarte; Kornelia Jumel; Francisco M. Gírio; Steven Harding; Graham W. Pettigrew; Isabel Moura (JBIC Journal of Biological Inorganic Chemistry, 2003)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)